Final analysis of the international observational S-Collate study of peginterferon alfa-2a in patients with chronic hepatitis B - Marcellin, Patrick; Xie, Qing; Woon Paik, Seung; Flisiak, Robert; Piratvisuth, Teerha; Petersen, Jörg; Asselah, Tarik; Cornberg, Markus; Ouzan, Denis; Foster, Graham R; Papatheodoridis, Georgios; Messinger, Diethelm; et al. (PLoS One, 2020)
BACKGROUND AND AIMS: Sustained off-treatment immune control is achievable in a proportion of patients with chronic hepatitis B treated with peginterferon alfa-2a. We evaluated on-treatment predictors of hepatitis B surface antigen (HBsAg) clearance 3 years after peginterferon alfa-2a treatment and determined the incidence of hepatocellular carcinoma. METHODS: A prospective, international, multicenter, observational study in patients with chronic hepatitis B who have been prescribed peginterferon alfa-2a (40KD) in a real-world setting. The primary endpoint was HBsAg clearance after 3 years' follow-up. RESULTS: The modified intention-to-treat population comprised 844 hepatitis B e antigen (HBeAg)-positive patients (540 [64%] completed 3 years' follow-up), and 872 HBeAg-negative patients (614 [70%] completed 3 years' follow-up). At 3 years' follow-up, HBsAg clearance rates in HBeAg-positive and HBeAg-negative populations, respectively, were 2% (16/844) and 5% (41/872) in the modified intention-to-treat population and 5% [16/328] and 10% [41/394] in those with available data. In HBeAg-positive patients with data, Week 12 HBsAg levels <1500, 1500-20,000, and >20,000 IU/mL were associated with HBsAg clearance rates at 3 years' follow-up of 11%, 1%, and 5%, respectively (Week 24 predictability was similar). In HBeAg-negative patients with available data, a ≥10% decline vs a <10% decline in HBsAg at Week 12 was associated with HBsAg clearance rates of 16% vs 4%. Hepatocellular carcinoma incidence was lower than REACH-B (Risk Estimation for Hepatocellular Carcinoma in Chronic Hepatitis B) model predictions. CONCLUSIONS: Sustained off-treatment immune control is achieved with peginterferon alfa-2a in a real-world setting. HBsAg clearance 3 years after completion of peginterferon alfa-2a can be predicted on the basis of on-treatment HBsAg kinetics.
Keywords: dospělí; Hepatitis B Surface Antigens; Female; Safety; interferon alfa; Adult; výsledek terapie; ženské pohlaví; hepatitida B - antigeny povrchové; Polyethylene Glycols; Internationality; hepatitida B - antigeny e; lidé; rekombinantní proteiny; Recombinant Proteins; internacionalita; Treatment Outcome; chronická hepatitida B; polyethylenglykoly; Male; Interferon-alpha; Hepatitis B e Antigens; bezpečnost; mužské pohlaví; Hepatitis B, Chronic; Humans